Reliability of a novel serious game using dual-task gait profiles to early characterize aMCI - Tarnanas, Ioannis; Papagiannopoulos, Sotirios; Kazis, Dimitris; Wiederhold, Mark; Widerhold, Brenda; Tsolaki, Magda (Frontiers in Aging Neuroscience, 2015)
Background: As the population of older adults is growing, the interest in an easy way to carefully characterize amnestic mild cognitive impairment (aMCI), a preclinical stage of Alzheimer's disease (AD), is becoming increasingly important. Serious Game (SG) based cognitive and motor performance profiles while performing everyday activities and Dual-Task Walking (DTW) "motor signatures" is two very promising markers, which can be detected in predementia states. We aim to compare the consistency, or conformity, of measurements made by a custom SG with DTW (NAV), a SG without DTW (DOT), neuropsychological measures and genotyping as markers to early characterize aMCI. Methods: The study population included three groups: early AD (n = 86), aMCI (n = 65) and healthy control subjects (HCS) (n = 76), who completed the custom serious game tasks, on three separate sessions over a three-month period. Outcome measures were neuropsychological data across-domain and within-domain Intra-Individual Variability (IIV) and DOT and NAV latency-based and accuracy-based IIV. Test–retest reliability of DOT and NAV markers were assessed using an intraclass correlation (ICC) analysis. Results: Results indicated that performance data, such as the NAV latency-based and accuracy-based IIV during the task displayed greater reliability across sessions compared to DOT. During the NAV task-engagement, the executive function, planning and motor performance profiles exhibited good reliability (ICC = 0.6–0.8), while during DOT, executive function and spatial memory accuracy profiles exhibitedmoderate reliability (ICC = 0.3–0.6). Additionally, reliability across tasks was more stable when three sessions were used in the ICC calculation relative to two sessions. Discussion: Our findings suggest that “motor signature” data during the NAV tasks was a more reliable marker for early diagnosis of aMCI than DOT. This result accentuates the importance of utilizing motor performance data as a metric for aMCI.